2012
DOI: 10.1021/cs300127w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Zeolite-Catalyzed Isomerization and Disproportionation of m-Xylene

Abstract: The mechanisms of m-xylene isomerization and disproportionation over 13 medium-pore zeolites and three large-pore ones are investigated. While H-TNU-10 and H-ZSM-57 with intersecting 10-and 8-ring channels were found to show considerably higher p/o ratios than H-ZSM-5, a commercial m-xylene isomerization catalyst, the GC-MS results from used zeolite catalysts demonstrate the intrazeolitic build-up of tri-and tetramethylated diphenylmethane species, whose existence during the m-xylene transformation over any ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 56 publications
7
79
3
1
Order By: Relevance
“…While the latter group of bicyclic aromatic compounds was found to be intermediates of iPB dehydrogenation, a side reaction of the iPB disproportionation, both groups of them are hardly observed over medium-pore zeolites, regardless of their structure type. However, we were not able to detect any di-iso-propylated 2,2-diphenylpropane (dipDP) species in this study, unlike the disproportionation of other aromatic hydrocarbons, including m-xylene, ethylbenzene, and n-propylbenzene, 12,17,18 in which formation of dialkylated diphenylalkane species as reaction intermediates has been clearly confirmed. To better understand the results described above, we have calculated the strain energies of three mipDP, three mip = DP, or six dipDP isomers embedded within the structures of zeolites studied, together with the relative energies of all species (i.e., reactant, reaction intermediates, transition states, and products) in the 84T H-Y model, using the mixed quantum-mechanical and semi-empirical ONIOM method.…”
Section: Introductioncontrasting
confidence: 67%
See 2 more Smart Citations
“…While the latter group of bicyclic aromatic compounds was found to be intermediates of iPB dehydrogenation, a side reaction of the iPB disproportionation, both groups of them are hardly observed over medium-pore zeolites, regardless of their structure type. However, we were not able to detect any di-iso-propylated 2,2-diphenylpropane (dipDP) species in this study, unlike the disproportionation of other aromatic hydrocarbons, including m-xylene, ethylbenzene, and n-propylbenzene, 12,17,18 in which formation of dialkylated diphenylalkane species as reaction intermediates has been clearly confirmed. To better understand the results described above, we have calculated the strain energies of three mipDP, three mip = DP, or six dipDP isomers embedded within the structures of zeolites studied, together with the relative energies of all species (i.e., reactant, reaction intermediates, transition states, and products) in the 84T H-Y model, using the mixed quantum-mechanical and semi-empirical ONIOM method.…”
Section: Introductioncontrasting
confidence: 67%
“…Details of the IR measurements with adsorbed pyridine can be found elsewhere. 17,18,22 After desorption at 473 K for 2 h, the concentrations of Brønsted and Lewis acid sites in zeolites were determined from the intensities of the IR bands around 1550 and 1450 cm -1 , respectively, using the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 equations of Emeis. 23 The characterization data for zeolite catalysts studied here are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably, the decomposition of PC contribute to not only the formation of C 3 species, but also C 2 and C 4 species, similar to the disproportionation reaction in other systems. 21,22 The disproportionation of C 3 H 6 on AC is possible under an electrocatalytic condition and in the presence of H 2 . In addition, the data in 2 nd and 3 rd cycles indicated that the percentage of CH 4 decreased a little bit, but the percentage of C 3 H 6 and C 3 H 8 remained nearly the same.…”
Section: Methodsmentioning
confidence: 99%
“…Es, por tanto, importante, considerar que tipo de reacciones pueden ocurrir tanto en los canales de 10 como en las intersecciones, con el fin de ver las consecuencias del tráfico molecular. Considerando este escenario, donde los canales de La prueba de que esta reacción ocurre en las intersecciones de los canales de 10 es que también se da en zeolitas con canales de poro medio tales como la MFI 58,121,122 , la MEL 120 y la TNU 120 , cuyas dimensiones de canales son similares a alguno de los canales de 10 de la UWY (Figura 3.42).…”
Section: Tráfico Molecular En La Uwyunclassified